Pengaruh Membaca Alquran terhadap Kestabilan Emosi pada Mahasiswa di Bukittinggi - Ikhsan, Alfi Khairul; Akbar, Zidan Maliki; Oktari, Dela; Dira, Laura Farah; Andini, Juwita Putri; Fitra, Ilham; Alwi, Muhammad Habib (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2025)
This research aims to examine the effect of reading the Koran on the emotional stability of students in Bukittinggi. This research approach is quantitative with a causal design with regression analysis methods. The sample used was 122 students selected at simple random. The results of the analysis show that there is a significant influence between reading the Koran and students' emotional stability. There is a value of 10.9% indicating that reading the Koran contributes to emotional stability. This research supports previous findings that reading the Koran has a positive impact on mental health and emotional stability.